2018
DOI: 10.1556/032.2018.68.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Do institutions still matter for investors? Impact of institutional determinants on investment inflows into European economies

Abstract: Institutional quality is commonly cited as a reason that investment infl ows still vary across European countries, despite their economic stabilization following the tumultuous years in the early 1990s. This article tests empirically whether institutional quality has any bearing on the level of investment infl ows into selected groups of European countries. The role of institutions is assessed using Economic Freedom indices from the Heritage Foundation. We construct a panel dataset from 2000–2015 for 35 Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This was confirmed by existing research on the topic, e.g. Donu and Janíčko (2018). The multicollinearity was generally low in the model as the highest Variance Inflation Factor reached a maximum of 4 in case of GDP growth which is still a reasonable value.…”
Section: China and The Cee Regionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was confirmed by existing research on the topic, e.g. Donu and Janíčko (2018). The multicollinearity was generally low in the model as the highest Variance Inflation Factor reached a maximum of 4 in case of GDP growth which is still a reasonable value.…”
Section: China and The Cee Regionsupporting
confidence: 84%
“…Botrić and Škuflić (2005) assert that openness of the country and overall economic development is the most important factor positively influencing ODI in Balkan countries. Kersan-Škabić (2013) and Donu and Janíčko (2018) focused on institutional determinants of ODI in CEE countries when performing a regression analysis of macroeconomic data and their results are similarly stating that institutional variables, such as business and investment freedom or a good regulatory framework, are important determinants for attracting ODI, yet by far not crucial. Somewhat less recent research conducted by Korniyenko and Sakatsume (2009) examined Chinese ODI in the EBRD's countries and concluded that driving motives are resource-seeking and market-seeking, with strategic-asset-seeking motivation rising in last years of the study.…”
Section: China and The Cee Regionmentioning
confidence: 97%